Probiotics: A gut response to the COVID-19 pandemic but what does the evidence show?. (October 2022) - Brahma, Sandrayee; Naik, Amruta; Lordan, Ronan
Summary: Since the global outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), research has focused on understanding the etiology of coronavirus disease 2019 (COVID-19). Identifying and developing prophylactic and therapeutics strategies to manage the pandemic is still of critical importance. Among potential targets, the role of the gut and lung microbiomes in COVID-19 has been questioned. Consequently, probiotics were touted as potential prophylactics and therapeutics for COVID-19. In this review we highlight the role of the gut and lung microbiome in COVID-19 and potential mechanisms of action of probiotics. We also discuss the progress of ongoing clinical trials for COVID-19 that aim to modulate the microbiome using probiotics in an effort to develop prophylactic and therapeutic strategies. To date, despite the large interest in this area of research, there is promising but limited evidence to suggest that probiotics are an effective prophylactic or treatment strategy for COVID-19. However, the role of the microbiome in pathogenesis and as a potential target for therapeutics of COVID-19 cannot be discounted.